2023
DOI: 10.1101/2023.03.01.530513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid molecular phenotypic antimicrobial susceptibility test forNeisseria gonorrhoeaebased on propidium monoazide viability PCR

Abstract: Neisseria gonorrhoeae(NG) is an urgent threat to antimicrobial resistance (AMR) worldwide. NG has acquired rapid resistance to all previously recommended treatments leaving ceftriaxone monotherapy as the first and last line of therapy for uncomplicated NG. The ability to rapidly determine susceptibility, which is currently nonexistent for NG, has been proposed as a strategy to preserve ceftriaxone by using alternative treatments. Herein, we used a DNA-intercalating dye in combination with NG-specific primers/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous research has indicated that chronic infection can persist despite antibiotic use and negative culture results due to the presence of VBNC bacteria (33). These findings highlight the limitations of culture techniques and the need for more advanced molecular techniques, which offer greater sensitivity, specificity, and efficiency (34,35). While some studies continue to advocate for the culture approach, many confirm the precision and effectiveness of the PCR method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has indicated that chronic infection can persist despite antibiotic use and negative culture results due to the presence of VBNC bacteria (33). These findings highlight the limitations of culture techniques and the need for more advanced molecular techniques, which offer greater sensitivity, specificity, and efficiency (34,35). While some studies continue to advocate for the culture approach, many confirm the precision and effectiveness of the PCR method.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR can detect both the genus and species of bacteria and provide a precise quantification, while the culture method only detects the genus, and further biochemical and sugar fermentation studies are required for species identification, leading to longer turnaround times (33,34). To reliably detect a signal, a sufficient concentration of DNA is necessary, and the limit of detection indicates the lowest DNA concentration that can be reliably distinguished from a blank sample (35). The sensitivity of a test reflects its ability to correctly identify a patient, with higher sensitivity leading to a lower false negative rate and better identification of disease cases (36).…”
Section: Discussionmentioning
confidence: 99%